Understanding professionals' perspectives and experiences of elder self‐neglect: A systematic review and meta‐synthesis of qualitative studies. Issue 1 (17th November 2021) - Yu, Mingming; Ramachandran, Hadassah Joann; Qian, Min; Shi, Yuexian; Gu, Libin; Wang, Wenru
Abstract: Purpose: To systematically review and synthesize the findings on various professionals' perspectives of elder self‐neglect (ESN) and/or their experiences with ESN. Design: A systematic qualitative review was used. Methods: Primary qualitative studies published either in English or Chinese until August 2020 were systematically searched in the following databases: PubMed, Web of Science, Embase, CINAHL Plus, PsycINFO, Wanfang Data, and China National Knowledge Infrastructure (CNKI). Findings: Eleven studies were included. Five subthemes including retaining a sense of normalcy/identity, service refusal, isolation, contributing factors in ESN, and manifestations and consequences of ESN were included in the overarching theme of ESN features. Another two subthemes, emotional and ethical dilemmas in caring for self‐neglecters and management strategies, were included under the second overarching theme of complicated experiences managing cases of ESN. Conclusions: This qualitative synthesis provides a deep and comprehensive insight into professionals' perspectives and experiences of self‐neglect in older adults. Understanding professionals' perspectives of ESN can help with the knowledge and theory development pertinent to this particular phenomenon. Clinical relevance: Findings are valuable in informing the provision of funds and structural, informational, and emotional support systems development for professionals managing ESN cases. Establishing a strong link between ESN case management and improved outcomes in older self‐neglecters is essential to establish a definite need for the provision of support, resource, and stardardized guidelines for these professionals.